1972
DOI: 10.1111/j.1545-5300.1972.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the Stresses of Travel as an Opportunity for Improving the Quality of Work and Family Life

Abstract: The relationship between the working lives and family lives of people in our society is little explored. This article describes a case in which heavy business travel created problems both for the industrial organization and the families of the employees involved. To cope with the problem, the family perspective was brought into the organization by means of a husband‐wife workshop. The workshop used structure to fit privacy norms of industry, to help couples explore aspects of their relationships that determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…An examination of these 11 studies reveals a rather odd selection of studies of varying methodological rigor and mixed outcomes and whose results do not appear to fully justify the conclusion drawn by Burke. One was an unpublished dissertation (Campbell, 1973), two provided no quantitative data (Falconer and Hornick, 1983;Blake and Mouton, 1984), a fourth was not an evaluation of an intervention (Pierce and Newstom, 1983), and two further studies were individually orientated interventions, not organizational interventions (Culbert and Renshaw, 1972;Ganster et al, 1982). Of the remaining ®ve studies, Quick (1979) reported signi®cant changes in role con¯ict and role ambiguity but not in absence 5 and 8 months after a goal-setting intervention.…”
Section: Examples Of the Evidencementioning
confidence: 98%
“…An examination of these 11 studies reveals a rather odd selection of studies of varying methodological rigor and mixed outcomes and whose results do not appear to fully justify the conclusion drawn by Burke. One was an unpublished dissertation (Campbell, 1973), two provided no quantitative data (Falconer and Hornick, 1983;Blake and Mouton, 1984), a fourth was not an evaluation of an intervention (Pierce and Newstom, 1983), and two further studies were individually orientated interventions, not organizational interventions (Culbert and Renshaw, 1972;Ganster et al, 1982). Of the remaining ®ve studies, Quick (1979) reported signi®cant changes in role con¯ict and role ambiguity but not in absence 5 and 8 months after a goal-setting intervention.…”
Section: Examples Of the Evidencementioning
confidence: 98%
“…Few empirical studies report attempts by organizations to assist their employees in dealing with specific occupational demands. Among these, Culbert and Renshaw (1972) and Renshaw (1975) describe and evaluate workshops designed to reduce demands due to (1) travel requirements of particular managerial jobs and (2) temporary relocations to other countries as part of one's career progress. Campbell (1973) offers a model and rationale for an attempt to improve the personenvironment fit in a field study.…”
Section: Discussionmentioning
confidence: 99%
“…Organizations must develop mechanisms for integrating the family perspective into relevant organizational decisions. One example of how this has been done is described in Culbert and Renshaw (6). A joint, problem-solving approach on the part of both systems is suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Having defined his absences as the cause of their problem, he then spent much energy worrying about the effects of his travel, envisaging the only solution as giving up traveling, and ultimately his present job. Until they participated in a workshop focused on the stresses of travel, (Culbert and Renshaw [6]), they were stuck with that causal explanation, which led to a dead end. During the workshop, they were each able to question their causal definition of the situation and entertain alternative solutions.…”
Section: The Creation Of Stressmentioning
confidence: 99%